Compressive behaviour of double skin sections with stainless steel outer tubes and recycled aggregate concrete. (July 2022) - Castanheira, D.S.; de Lima, L.R.O.; da S. Vellasco, P.C.G.; Cashell, K.A.; Gardner, L.
Abstract: An experimental and numerical study into the behaviour of concrete-filled double skin tubular (CFDST) stub columns is presented. A total of eight axial compression tests were carried out, four utilising conventional concrete and four with recycled aggregate concrete. The stub columns were circular in cross-section and each comprised an austenitic stainless steel outer tube and a carbon steel inner tube, of varying dimensions. Accordingly, hollow ratios of 0.67 and 0.55 were considered. The recycled coarse aggregate was made by crushing test specimens from a previous research project, and a replacement ratio of 50% was adopted. During the experiments, similar structural behaviour and failure modes were observed between the specimens with conventional and recycled aggregate concrete. To investigate the behaviour further, a finite element model was developed in ABAQUS; validation of the model against the experimental results from the current work as well as data available in the literature is described. The finite element model was employed to conduct a parametric study to examine the load-bearing contributions of the constituent components of CFDST sections and to assess the influence of the hollow ratio on the structural behaviour. The experimental and numerical ultimate loads are compared with the capacity predictions determined using available design procedures. Overall, the results show that CFDST stub columns with recycled aggregate concrete can achieve similar capacities to their conventional concrete counterparts, demonstrating the potential for the wider use of recycled aggregate concrete, towards more sustainable structural solutions.